Sinking Speed Yarn PE (Polyethylene) is preserved With guava leaf extract (Psidium guajava L), papaya (Carica papaya) and betel leaves (Xylocarpus moluccensis M.Roem) - Suryadi, Dedi; Syofyan, Irwandy; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTHusband of research has been done in December 2014 gear Materials Laboratory of the Faculty of Fisheries and Marine Sciences, University of Riau Pekanbaru. Early studies aimed to determine the effect of guava leaf extract preservatives, papaya leaf, betel leaf and Against Speed sink (sink rate) Yarn PE. Initial studies using experimental methods with object using research is preserved Threads tested in the laboratory. Value Speed sink Yarn PE can be seen on Speed drowned in the sea Yarn berisih air tube. Speed maximum sink is necessary to look at the things that affect Extracts Against Speed heart sank sautu Yarn Material Test time is usually determined by the liver seconds. The difference from the average - average Speed with sink Yarn benangyang not well maintained preserved guava leaf extract as much as 0.89%, while the average difference - average Thread Thread unpreserved with papaya leaf extract's been preserved as much as 1.68%, and the difference Of Threads yet preserved yarns with Already preserved with betel leaf extract as much as 3.04%.Keywords: Conservation, Polyethylene Yarn, guava leaf extract (Psidium guajava L), papaya (Carica papaya) and betel leaves (Xylocarpus moluccensis M.Roem)